Obraz współczesnej młodzieży w Polsce. Studium socjologiczno-pastoralne - Pawlina, Krzysztof (Warszawskie Studia Teologiczne, 2018)
In the pastoral postulates, defining the role of the Church in upbringing, one has to emphasise three things. Firstly: what we need is good use of the media, especially the Internet, however we should not abandon personal contacts and meetings, because only them ensure the holistic formation of the world of faith based on the community of the Church. Secondly: some young people appreciate catechism. It requires careful preparation of catechists and the whole process of catechising. Thirdly: religiousness of young people is particularly changeable, prone to influences and moods. This requires patience. Accompanying young people includes not only catechising, but also witness of life and kind presence among the questions and problems of faith.